Technical player profiles related to the physical fitness of young female volleyball players predict team performance - Davila-Romero, C.; Hernandez-Mocholi, M. A.; Garcia-Hermoso, A. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: This study is divided into three sequential stages: identification of fitness and game performance profiles (individual player performance), an assessment of the relationship between these profiles, and an assessment of the relationship between individual player profiles and team performance during play (in championship performance).